1996
DOI: 10.1007/bf01795226
|View full text |Cite
|
Sign up to set email alerts
|

The membranous portion of the interventricular septum in neonates An anatomic study in neonatal cadavers

Abstract: The membranous portion of the interventricular septum (MPIS) has been described as a small, oval portion of the cardiac septum that lies immediately below the aortic valve. Its location and relationship with the aortic valve are very important in surgical interventions. Several studies have been reported in adults but few in neonates. For this reason, studies of the MPIS were made in the hearts of 26 (12 male, 14 female) fulterm neonates. The left side of the MPIS was photographed with transillumination from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The most prevalent VSD subtype is the perimembranous VSD [5], [6] which is characterized by the loss of the membranous part of the ventricular septum (VS) and a defect in the development of a second part of the VS - the muscular septum. Interestingly, the membranous VS does not start to grow before the muscular VS generation has been finished [7] indicating that membranous VS development is probably initiated by an interaction of the inlet muscular VS and the atrioventricular endocardial cushion cells (ECCs) [8], [9]. The membranous VS arises solely from the ECCs and not from the muscular VS [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent VSD subtype is the perimembranous VSD [5], [6] which is characterized by the loss of the membranous part of the ventricular septum (VS) and a defect in the development of a second part of the VS - the muscular septum. Interestingly, the membranous VS does not start to grow before the muscular VS generation has been finished [7] indicating that membranous VS development is probably initiated by an interaction of the inlet muscular VS and the atrioventricular endocardial cushion cells (ECCs) [8], [9]. The membranous VS arises solely from the ECCs and not from the muscular VS [4].…”
Section: Introductionmentioning
confidence: 99%
“…The muscular VS grows first, followed by the membranous VS. The membranous VS arises due to interactions between the muscular VS and the AV endocardial cushion cells (Icten and Tetik, 1996). Studies have shown that the membranous VS is derived from the AV endocardial cushion lineage, and that proper morphogenesis of the OFT cushions is required for proper alignment and movement of the AV cushions (Komatsu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fibrous portion of the IVMS closes 3 weeks later. Finally, the fused aortopulmonary septum and the fused atrioventricular cushions assemble the muscular portion of the interventricular septum [ 8 , 9 ].…”
Section: Embryological Origin Of the Ivmsmentioning
confidence: 99%